Sports biomechanical analysis of International Standard Dance: Movement techniques in Standard Dance - Wu, T.; Fu, P. (Journal of Human Sport & Exercise, 2025)
As a principal discipline within International Standard Dance, Standard Dance requires dancers to possess strong body control capabilities and a profound understanding of sports biomechanics due to the complexity of its technical movements and the demands for artistic expressiveness. This study adopts a sports biomechanical perspective, employing expert surveys, video analysis, and interdisciplinary research methods to investigate the fundamental techniques of Standard Dance - specifically rise and fall, weight transfer, contra body movement, swing, inclination, and rotation - with the aims of exploring the biomechanical principles underlying these techniques and their practical application in dance movements. The research findings indicate that the movement techniques of Standard Dance adhere to the fundamental principles of sports biomechanics. Specifically, the "S"-shaped kinetic chain transmission sequence in rise-and-fall techniques optimizes energy transfer efficiency, the dynamic balance control mechanism in weight transfer enhances dancers` stability, the conservation of angular momentum in contra body movement provides a mechanical foundation for rotational actions, the regulation of muscular torque in inclination techniques maintains dynamic equilibrium, the conversion between potential and kinetic energy in swing techniques enhances dance fluidity and artistic expressiveness, and the transfer of angular momentum in rotation techniques offers mechanical support for the execution of complex rotational movements. This study employs sports biomechanical principles to analyse the six core techniques of Standard Dance, revealing the biomechanical mechanisms underlying movement efficiency and artistic expressiveness, thereby providing a crucial theoretical foundation for the scientific refinement and precision-oriented optimization of technical training.